HASIL UJI EMPIRIK MODEL PENILAIAN AUTENTIK DALAM KOMPETENSI BERBICARA - Rahmawati, Laili (Universitas Ahmad Dahlan, 2015)
The reserch has aim to describe the result of empiric test of authentic assessment model in speaking competence. The method used in the research was the Research and Development method, i.e. a research method which used to produce a certain product, and examine the effectivity of the product. The research was belonging to the step of model examining. The model examining was conducted by experimenting the authentic assessment model of the speaking competence. The examination were conducted by testing the receiption view of the model developed through the trying out of the apply of assessment model and finding out the properity and its receiption through the statements exploration of the respondents and the expert which act as the lecturer of the speaking competence subject. The respondents or informants statement were acquired by comparing the preview assessment model and the assessment model proposed. Based on the result of the model testing, it can be concluded that by using the assessment rubric, the speaking competence of the students can be known through the various components of the speaking competence in a detail. The difference of the assessment between one jury to other represented that the scores were not too significant different. It means that the perception of the two juries toward the components material were almost equivalent. The condition showed that the objectivity of the assessment was in a high level.